INTEGRASI EPISTEMOLOGI ISLAM DAN SAINS BERBASIS TAUHID DALAM KURIKULUM - Ike Septia Wulandari; Nurhalimah; Umi Kulsum; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
This study examines the principle of tauhid as the philosophical foundation for integrating religious and scientific knowledge within the educational curriculum, particularly in Madrasah Ibtidaiyah (MI). The rapid advancement of science and technology in the digital era has created a dichotomy between religious and secular sciences, resulting in fragmented understanding among students. Islamic education requires a holistic paradigm that unites all branches of knowledge within the framework of divine values. The principle of tauhid emphasizes the unity of Allah as the source of all knowledge and serves as a conceptual basis for harmonizing religious teachings with scientific inquiry. This research employs a qualitative approach through library research by analyzing classical and contemporary literature on Islamic education, curriculum development, and the concept of knowledge integration. The findings indicate that the implementation of the tauhid-based curriculum can be realized through integrative learning, contextual teaching strategies, character education, and the incorporation of Islamic values into science subjects. Such an approach encourages students to develop spiritual awareness, scientific literacy, critical thinking skills, and moral responsibility simultaneously. Therefore, the principle of tauhid remains highly relevant as a philosophical foundation for developing an integrated curriculum that responds to contemporary educational challenges while maintaining Islamic values.